2021
DOI: 10.1002/aoc.6323
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole ligands with allyl, propargyl or allene groups, DNA binding properties, and molecular docking studies

Abstract: Three benzimidazole based tridentate ligands (L1–L3) and their mononuclear complexes with the general formula of [M(L)Cl2] (where M: Mn(II), Cu(II), and Zn(II), L: ligand) were prepared. The solid state structures of the ligands and [Cu(L1)Cl2], [Mn(L3)Cl2], and [Zn(L3)Cl2] complexes were determined by single crystal X‐ray diffraction studies. The X‐ray crystallographic data confirmed the tautomeric conversion of alkyne groups in L2 to allene isomer L3. In the structures of the complexes, each metal ion is fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The compound showed considerable binding affinities towards DNA, and their binding affinities are lower than those of standard DNA intercalating ( K b value of spermine and ethidium bromide are 2.1 × 10 5 and 8.1 × 10 4 M −1 , respectively) agents. [ 23 ] The UV–Vis spectral changes and binding constants ( K b ) suggest that the ligands and their Cu(II) and Zn(II) complexes interact with DNA in groove binding mode. [ 40 ] The ligand L 1 showed the highest binding properties with K b of 10 × 10 4 M −1 , and complexation of L 1 with Cu(II) and Zn(II) decreased the binding affinity of the free ligand.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The compound showed considerable binding affinities towards DNA, and their binding affinities are lower than those of standard DNA intercalating ( K b value of spermine and ethidium bromide are 2.1 × 10 5 and 8.1 × 10 4 M −1 , respectively) agents. [ 23 ] The UV–Vis spectral changes and binding constants ( K b ) suggest that the ligands and their Cu(II) and Zn(II) complexes interact with DNA in groove binding mode. [ 40 ] The ligand L 1 showed the highest binding properties with K b of 10 × 10 4 M −1 , and complexation of L 1 with Cu(II) and Zn(II) decreased the binding affinity of the free ligand.…”
Section: Resultsmentioning
confidence: 99%
“…It is informative to compare the DNA binding properties of the ligands with the similar ligands with different N‐substitute groups (allyl, propargyl or allene groups) reported by our group. [ 23 ] It was observed that the substitute groups on the 2,6‐bis(2‐benzimidazole)pyridine moiety as well as complexation of the ligands with different metal ions have affected the DNA binding properties. Moreover, the planarity of the pyridine and two side benzimidazole units also has an impact in the DNA binding affinities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Several imidazole derivatives and their metal complexes have also been reported to have promising DNA binding affinities. 19 Recently, quantum-mechanical calculations have been recognized as an important tool for predicting various characteristics like non-covalent interactions, HOMO–LUMO energies, and non-linear optical properties of various classes of compounds. In this context, our research group have reported the synthesis and computational investigations of various classes of compounds such as peptoids, 20 hydrazones, 21,22 chalcones and β-hydroxy carbonyl compounds, 22,23 functionalized esters, 24 piperidone derivatives, 25 functionalized pyrimidines, 26,27 phosphonates, 28 monocarbonyl curcuminoids, 29,30 functionalized indoles, 31 and unsymmetrical acyl thioureas, 32 as well as organic salt systems, 33,34 transition metal complexes, 11 etc.…”
Section: Introductionmentioning
confidence: 99%